Protein disulfide isomerase expression increases in resistance arteries during hypertension development. Effects on Nox1 NADPH oxidase signaling - Androwiki, Aline C. D.; Camargo, Lívia de Lucca; Sartoretto, Simone; Couto, Gisele K.; Ribeiro, Izabela M. R.; Veríssimo-Filho, Sidney; Rossoni, Luciana V.; Lopes, Lucia R. (Frontiers in Chemistry, 2015)
NADPH oxidases derived reactive oxygen species (ROS) play an important role in vascular function and remodeling in hypertension through redox signaling processes. Previous studies demonstrated that protein disulfide isomerase (PDI) regulates Nox1 expression and ROS generation in cultured vascular smooth muscle cells. However, the role of PDI in conductance and resistance arteries during hypertension development remains unknown. The aim of the present study was to investigate PDI expression and NADPH oxidase dependent ROS generation during hypertension development. Mesenteric resistance arteries (MRA) and thoracic aorta were isolated from 6, 8 and 12 week-old spontaneously hypertensive (SHR) and Wistar rats. ROS production (dihydroethidium fluorescence), PDI (WB, imunofluorescence), Nox1 and NOX4 (RT-PCR) expression were evaluated. Results show a progressive increase in ROS generation in MRA and aorta from 8 to 12 week-old SHR. This effect was associated with a concomitant increase in PDI and Nox1 expression only in MRA. Therefore, suggesting a positive correlation between PDI and Nox1 expression during the development of hypertension in MRA. In order to investigate if this effect was due to an increase in arterial blood pressure, pre hypertensive SHR were treated with losartan (20mg/kg/day for 30 days), an AT1 receptor antagonist. Losartan decreased blood pressure and ROS generation in both vascular beds. However, only in SHR MRA losartan treatment lowered PDI and Nox1 expression to control levels. In MRA PDI inhibition (bacitracin, 0.5 mM) decreased Ang II redox signaling (p-ERK 1/2). Altogether, our results suggest that PDI plays a role in triggering oxidative stress and vascular dysfunction in resistance but not in conductance arteries, increasing Nox1 expression and activity. Therefore, PDI could be a new player in oxidative stress and functional alterations in resistance arteries during the establishment of hypertension.